2012
DOI: 10.1016/j.freeradbiomed.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxynonenal-generated crosslinking fluorophore accumulation in Alzheimer disease reveals a dichotomy of protein turnover

Abstract: Lipid peroxidation generates reactive aldehydes, most notably hydroxynonenal (HNE), which covalently bind amino acid residue side chains leading to protein inactivation and insolubility. Specific adducts of lipid peroxidation have been demonstrated in intimate association with the pathological lesions of Alzheimer disease (AD), suggesting that oxidative stress is a major component of AD pathogenesis. Some HNE-protein products result in protein crosslinking through a fluorescent compound similar to lipofuscin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…In addition, the HNE lysine-derived pyrrole adducts (Fig 2B) were strongly, but not exclusively, associated with neurofibrillary tangle (NFT)-bearing neurons in LAD subjects (Montine et al 1997a; Montine et al 1997b; Sayre et al 1997). More recently, fluorophoric HNE modifications localized to neuronal cytoplasm, corresponding to grandovacular degeneration, were significantly elevated in the HIP of LAD subjects compared to age-matched NC subjects (Zhu et al 2012). HNE adduct colocalization with non-perivascular senile plaques was relatively weak (Sayre et al 1997) and reported in only a fraction of AD subjects (Ando et al 1998).…”
Section: Hydroperoxide Decomposition: Postmortemmentioning
confidence: 99%
“…In addition, the HNE lysine-derived pyrrole adducts (Fig 2B) were strongly, but not exclusively, associated with neurofibrillary tangle (NFT)-bearing neurons in LAD subjects (Montine et al 1997a; Montine et al 1997b; Sayre et al 1997). More recently, fluorophoric HNE modifications localized to neuronal cytoplasm, corresponding to grandovacular degeneration, were significantly elevated in the HIP of LAD subjects compared to age-matched NC subjects (Zhu et al 2012). HNE adduct colocalization with non-perivascular senile plaques was relatively weak (Sayre et al 1997) and reported in only a fraction of AD subjects (Ando et al 1998).…”
Section: Hydroperoxide Decomposition: Postmortemmentioning
confidence: 99%
“…Some of the free radicals thus generated escape; rather than appropriately transporting their electron to the next molecule in the cascade, they abandon the inner membrane of the mitochondria and impose alterations on other macromolecules within the cell. These alterations are often detrimental: DNA/RNA oxidation may yield fragmentation and deficiencies in repair machinery 32, 33 ; oxidative modification of enzymes and metabolic signaling proteins may lead to metabolic impairments 34 ; and protein cross-linkages and impaired proteolysis network resulting from oxidative modification may render proteins insoluble and prone to aggregate abnormally 3537 .…”
Section: Neuronal Oxidative Stress: Sources and Vulnerabilitiesmentioning
confidence: 99%
“…The best-studied reactive carbonyl is hydroxynonenal (HNE) [8] and one of its defined products is a fluorescent cross-link (HNE-fluorophore) between two lysines [12]. In AD, antibodies specific to HNE-fluorophore show its accumulation in the degradation pathway and granulovacuolar degeneration (GVD) in vulnerable neurons [13]. Additionally, HNE cross-links are seen in axons of AD and controls, as well as non-cross-linking HNE modifications [14].…”
Section: Introductionmentioning
confidence: 99%